A Tunable 3-Terminal GMR Device Based on a Hybrid Magnetic-Electric-Barrier Nanostructure. (22nd January 2013) - Kong, Y. H.; Chen, S. Y.; Zhang, G. L.; Fu, X.
Abstract : We propose a giant magnetoresistance (GMR) device, which can be experimentally realized by depositing two ferromagnetic (FM) strips and a Schottky metal (SM) stripe in parallel configuration on top of the GaAs heterostructure. The GMR effect ascribes a significant electron transmission difference between the parallel and antiparallel magnetization configurations of two FM stripes. Moreover, the MR ratio depends strongly on the magnetic strength of the magnetic barrier (MB) and the electric barrier (EB) height induced by an applied voltage to the SM stripe. Thus, this system can be used as a GMR device with tunable MR by an applied voltage to SM stripe or by magnetic strength of the MB.